2009
DOI: 10.1626/pps.12.37
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the Common Ice Plant,Mesembryanthemum crystallinumas a New High-Functional Food as Evaluated by Polyol Accumulation

Abstract: : We measured the concentration of polyols (pinitol, ononitol, and myo-inositol), which are known to have health-promoting and/or disease-preventing functions, in the common ice plant (Mesembryanthemum crystallinum L.) cultured under salt-and drought-stressed treatments. In NaCl-treated plant the concentration of pinitol/ononitol increased with increasing NaCl concentration in culture solution. The maximal concentration was 3.6 mg g -1 FW, which was found in the shoot top, followed by small side shoots (2.1 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 36 publications
(44 reference statements)
1
50
0
4
Order By: Relevance
“…Plant culture and NaCl treatment Seeds of M. crystallinum L. were surface-sterilized and sowed on germination medium as described by Agarie et al (2007). Seedlings were transferred to pots and grown in a greenhouse in Kagawa University according to the description by Agarie et al (2009). NaCl was applied to the 4-week-old plants by irrigation of nutrient solutions 'Otsuka House No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant culture and NaCl treatment Seeds of M. crystallinum L. were surface-sterilized and sowed on germination medium as described by Agarie et al (2007). Seedlings were transferred to pots and grown in a greenhouse in Kagawa University according to the description by Agarie et al (2009). NaCl was applied to the 4-week-old plants by irrigation of nutrient solutions 'Otsuka House No.…”
Section: Methodsmentioning
confidence: 99%
“…The growth enhancement of the ice plant in salinized soils is observed at around 100-200 mM NaCl (Adams et al, 1998;Flowers, Troke & Yeo, 1977). This halophyte has been cultivated as vegetables in some countries (Agarie et al, 2009), and also used as a model system for various studies on salt tolerance (Vera-Estrella et al, 1999. However, there has been no information on the mechanisms of halophilism in this species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mesembryanthemum crystallinum L., the common ice plant, is a leafy vegetable crop (Agarie et al, 2009) that exhibits extreme tolerance to high salinity concentrations equivalent to seawater (ca. 500 mM NaCl).…”
Section: Introductionmentioning
confidence: 99%
“…Their natural and food materials, however, were restricted to common foods. On the other hand, petals of carnations 7 and ice plants 4 contain pinitol, and it was demonstrated that pinitol in the plants acts as an osmotic regulator and cryoprotectant in cells. 8 Thus, many plants are expected to contain inositols.…”
Section: ■ Introductionmentioning
confidence: 99%